Hacia una tipología de asentamientos informales (2016)
This article is aimed at establishing a typology of informal settlements in the city of Montería from two points of view: 1) origin of the settlement, and 2) urban state of such settlements. The grading given to 35 subnormal neighborhoods by the Land Regulation Plan (POT in Spanish) 2002 – 2015, is the starting point for this research which takes as referents the works about marginal informal, irregular and spontaneous settlements of authors such Busquets, Clichevsky, Duhau, Lovera and Torres, among others; who frame those neighborhoods as developing in the margins of urban planning. Such a classification was achieved by means of a process of theoretical revision and a process of verification in the field which yielded enough elements to determine differentiating characteristics. Documental sources include the aforementioned Land Regulation Plan of Monteria 2002 – 2015, the Land Regulation Plans from 2000 to 2011 as well as the results of research processes conducted in other geographical contexts. Among the main findings, and according to the origin of the settlement in which the settlements arise, three identified typologies are highlighted: 1) settlement by means of invasion; 2) settlement by irregular private fragmentation; and 3) settlement by public fragmentation. Also, three types of typology from the urban point of view are identified: 1) precarious settlements; 2) semiconsolidated settlements and, 3) consolidated settlements. The current work is the product of a doctoral thesis on urban studies and its results are addressed to both scientific communities and local authorities on demand. © Architecture, City and Environment.